Metode Pembelajaran Tipe Student Teams Achievement Division Digunakan Dalam Upaya Meningkatkan Hasil Belajar Matematika Pada Materi Bangun Ruang Kelas Ix -F - Rohani Rohani (Jurnal Pendidikan Indonesia, 2022)
Cooperative Learning Method Type "Student Teams Achievement Division" (STAD) is used in an effort to improve mathematics learning outcomes in Class IX-F Students of SMP Negeri 80 Jakarta Odd Semester TP. 2017/2018 The researcher conducted this research with the aim of improving mathematics learning outcomes in class IX-FSMP Negeri 80 Jakarta students in the odd semester of the 2017/2018 school year. The learning method chosen in an effort to improve learning outcomes is the Student Teams Achievement Divisions (STAD) cooperative learning method, in which students learn independently through teacher guidance. While the research method used is Classroom Action Research (CAR). This research was conducted in two cycles. Each cycle consists of planning, implementing, observing, testing, analyzing and reflecting. The instruments used are learning instruments and data collection instruments. The learning instruments are in the form of lesson plans, teaching materials and worksheets, while the data collection instruments are in the form of test and non-test instruments in the form of questionnaires and observation sheets. After following the learning process using the STAD Method for two cycles of Mathematics, the results showed a very significant increase in learning outcomes. This can be seen from the test results, namely the average value in the pre-cycle was 55.11, increased sharply to 75.05 in the first cycle, then increased again in the second cycle which reached 78.30. When compared between the average value in the pre-cycle and the end of the second cycle, the average value increased by 42%. The level of completeness (with a KKM of 75) also shows the same thing, namely in the pre-cycle at first it was only 29.73%, then jumped drastically to 72.97% in the first cycle and continued to increase to 86.49%. at the end of the second cycle. Thus the use of the STAD method, the level of completeness increased by 191% compared to using the conventional method used in the pre-cycle or before the research was conducted